Pola Komunikasi Organisasi dalam Pembinaan Kader - Muhammad Amrillah; Bagus Sujatmiko; M. Muchsimi Ghozali (Bahasa Indonesia, 2025)
The background problem of this research is that there are many problems and obstacles faced in realizing organizational activities in the Ansor youth movement, namely: lack of organizational discipline, lack of guidance to Ansor members, differences of opinion and indications of inter-personal conflicts that cause slow implementation of these activities. This research is a qualitative research with the type of library research with the method of analysis (Content Analysis) after the data is collected the data is analyzed and then the data is analyzed and studied carefully and described which then provides a description and explanation and described the organizational communication patterns in the development of Ansor youth movement Banjar Anyar Village Branch Tanjung Anom District Nganjuk Regency. The results showed that the communication pattern applied in this organization is a combination of wheel and star pattern. The direction of communication includes vertical communication up and down, horizontal communication, and informal communication which is dominantly familial in nature. Communication barriers faced include member absence, information delays and differences in perception. The coaching strategy is carried out through personal and informal approaches that prioritize family values and togetherness. Communication not only functions as a conveyor of information, but also becomes the main media in the process of coaching.